Precisely rectilinear electro-thermal microactuator using a high-aspect ratio microstructured Si/SU-8 composite - Thubthimthong, Borriboon (2013)
This paper presents a Si/SU-8 composite electro-thermal microactuator that can generate a precisely rectilinear in-plane stroke. The microactuator consists of a pair of electro-thermally activated composite bimorphs which are joined at their tips through a central Si beam. When activated, the central beam deflects and outputs an in-plane rectilinear stroke at its center. The central stroke is precisely rectilinear along the plane of symmetry due to very high stiffness in the orthogonal directions to the stroke. This composite thermal microactuator produces a much larger rectilinear stroke and blocked force per unit temperature rise compared to an all-silicon one. At a temperature rise below 87 °C (driven below 8.0 V), the stroke increases linearly with the temperature rise up to 8.0 µm. Analytical and finite element models are developed for this range of actuation. Beyond an 87 °C temperature rise, the stroke was further enhanced by Poisson's ratio effect on SU-8 which increases the effective coefficient of thermal expansion of the composite. The microactuator could produce a maximum rectilinear stroke of 42 µm and a maximum estimated blocked force of 60 mN at a driving voltage of 14.5 V which causes a SU-8 average temperature rise of 266 °C.